Kerjasama Liberal Keantariksaan Antara Indonesia-India Dalam Pengembangan Teknologi Antariksa - Nurannisa Nadya Firdaus; Nurmasari Situmeang; Sindy Yulia Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the history that starts from the beginning of civilization to enter the present timeline, it is known that living things have only two footholds in this world, namely land and sea. But entering the middle of the 20th century, a foothold other than land and sea emerged, called space, which attracted the attention of many parties because it was believed to have resources where technology could adapt. These resources are the target of many countries because they can be used to become a forum for developing a technology. One of them is Indonesia, a country that wants to develop its space technology to realize its goals. Indonesia seeks to fulfill and advance the interests of its country through cooperative relations with other countries such as India. In this discussion, the main focus of the reading is that this research describes Indonesia's space cooperation with India, which aims to fulfill the interests of the country's resources. The research method used in this research is descriptive research, which refers to a qualitative case study. References from bilateral cooperation relations and space power are used to analyze the application of this space cooperation. Judging from the explanation above, this research shows that there are no concrete results from the continuation of the implementation of Indonesia-India space cooperation on the development of Indonesia's space technology.